Effects of focal brain cooling on extracellular concentrations of neurotransmitters in patients with epilepsy. (22nd February 2017) - Nomura, Sadahiro; Inoue, Takao; Imoto, Hirochika; Suehiro, Eiichi; Maruta, Yuichi; Hirayama, Yuya; Suzuki, Michiyasu
Summary: Objective: Brain hypothermia controls epileptic discharge and reduces extracellular concentrations of glutamate (Glu), an excitatory neurotransmitter. We aimed to determine the effects of focal brain cooling (FBC) on levels of γ‐aminobutyric acid (GABA), which is a major inhibitory neurotransmitter. The relationship between Glu or GABA concentrations and the severity of epileptic symptoms was also analyzed. Methods: Patients with intractable epilepsy underwent FBC at lesionectomized (n = 11) or hippocampectomized (n = 8) regions at 15°C for 30 min using custom‐made cooling devices. Concentrations of Glu (n = 18) and GABA (n = 12) were measured in extracellular fluid obtained through microdialysis using high‐performance liquid chromatography (HPLC). The reduction rate of neurotransmitter levels and its relationship with electrocorticography (ECoG) signal changes in response to FBC were measured. Results: We found no relationship between the concentrations of Glu or GABA and seizure severity. There was a significant decrease in the concentration of Glu to 66.3% of control levels during the cooling period (p = 0.001). This rate of reduction correlated with ECoG power (r 2 = 0.68). Cortical and hippocampal GABA levels significantly (p = 0.02) and nonsignificantly decreased to 47.7% and 32.4% of control levels, respectively. However, the rate of this reduction did not correlate with ECoG (r 2 = 0.11). Significance: Although the decrease in hippocampal GABA levels was not significant due to wide variations in its concentration, the levels of cortical GABA and Glu were decreased following FBC. FBC suppresses epileptic discharge and the release of both excitatory and inhibitory neurotransmitters. The reduction in Glu levels further contributes to the reduction in epileptic discharge. However, the reduction in the levels of GABA has no impact on ECoG.